2019
DOI: 10.1128/aac.01007-19
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Study of the Real-World Use of Ceftaroline versus Vancomycin for Acute Bacterial Skin and Skin Structure Infections

Abstract: The objective of this study was to determine if real-world ceftaroline treatment in adults hospitalized for acute bacterial skin and skin structure infections (ABSSSI) is associated with decreased infection-related length of stay (LOSinf) compared to that with vancomycin. This was a retrospective, multicenter, cohort study from 2012 to 2017. Cox proportional hazard regression, propensity score matching, and inverse probability of treatment weighting (IPTW) were used to determine the independent effect of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Infusion reactions have also less been described with telavancin, dalbavancin, and oritavancin. Other true AEs may include vancomycin nephrotoxicity [ 54 , 55 ] or elevated serum creatin-phosphokinase or rhabdomyolysis with daptomycin (2.8–3%) [ 56 , 57 ]. Data on newer lipoglycopeptide drugs indicate that dalbavancin showed reduced AEs in soft-tissue infections [ 58 ], with less nausea, diarrhea, and pruritus [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Infusion reactions have also less been described with telavancin, dalbavancin, and oritavancin. Other true AEs may include vancomycin nephrotoxicity [ 54 , 55 ] or elevated serum creatin-phosphokinase or rhabdomyolysis with daptomycin (2.8–3%) [ 56 , 57 ]. Data on newer lipoglycopeptide drugs indicate that dalbavancin showed reduced AEs in soft-tissue infections [ 58 ], with less nausea, diarrhea, and pruritus [ 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“… 32 Furthermore, a multicenter, retrospective, comparative cohort study in adults with ABSSSI found that discharge readiness at day 3 was higher in patients receiving ceftaroline fosamil than those receiving vancomycin; however, no differences in infection-related length of stay were demonstrated. 34 The variations in the reported impact of ceftaroline fosamil on healthcare resource use across these analyses may reflect differences in the patients studied, the design of the analyses, and in healthcare services in Europe and Latin America compared with the USA. 35 …”
Section: Discussionmentioning
confidence: 99%